Interaction of Ethanolamine with Magnetite Through Molecular Dynamic Simulations - Nikoleta Ivanova; Vasil Karastoyanov; Iva Betova; Martin Bojinov (Molecules)
Magnetite (Fe3O4) provides a protective corrosion layer in the steam generators of nuclear power plants. The presence of monoethanolamine (MEA) in coolant water has a beneficial effect on corrosion processes. In that context, the adsorption of MEA and ethanol–ammonium cation on the {111} surface of magnetite was studied using the molecular dynamics (MD) method. A modified version of the mechanical force field (ClayFF) was used. The systems were simulated at different temperatures (423 K; 453 K; 503 K). Surface coverage data were obtained from adsorption simulations; the root-mean-square deviation (RMSD) of the target molecules were calculated, and their minimum distance to the magnetite surface was traced. The potential and adsorption energies of MEA were calculated as a function of temperature. It has been established that the interaction between MEA and magnetite is due to electrostatic phenomena and the adsorption rate increases with temperature. A comparison was made with existing experimental results and similar MD simulations.